Invigoration of deteriorated seeds with cathodic water, ascorbic acid and other seed priming agents - Fatokun, Kayode (International Journal of Innovative Research and Scientific Studies, 2025)
A greenhouse pot experiment was conducted to compare the efficacy of cathodic water and ascorbic acid seed priming on the emergence and growth of deteriorated seeds of pea and pumpkin. Treatments that were investigated alongside cathodic water included cathodic water with pH adjusted to 7, calcium magnesium solution, calcium magnesium solution (with pH adjusted to 11), and distilled water. Electrolyte leakages from both the fresh and deteriorated seeds were also investigated. The study was conducted by subjecting seeds of the test species to controlled deterioration in an oven at 40°C for 32 days. The deteriorated seeds were thereafter invigorated with cathodic water, ascorbic acid, and other treatments. Fresh seeds of both species served as the control. The results indicated that electrolyte leakage from the deteriorated seeds was significantly higher than that of fresh seeds in both species. Invigorating the seeds with cathodic water led to significant (p < 0.05) emergence in both pea and pumpkin. Although all the treatments led to an improvement in both emergence and growth in both species, seeds treated with cathodic water generally performed best when compared with other treatments. More improvement in emergence and growth was also observed with pumpkin when compared with pea. While the successful invigoration of the deteriorated seeds, which led to the emergence and subsequent growth, may be linked to cell repairs and other biochemical changes in the invigorated seeds (not investigated in this study), the positive effects on the growth and biomass of the plant may be associated with improvements in chlorophyll content and chlorophyll fluorescence in pumpkin, and an increase in chlorophyll content in pea.